(untitled) - B J Smith (London, 1996)
The book provides a detailed and comprehensive introduction to the principles and practice of acoustics and noise control, including the measurement of sound; aural environment; room acoustics; structure-and-air-borne sound; vibration; noise control engineering; instrumentation; and law. It also includes an extensive bibliography along with an expanded glossary
Keywords: acoustical engineering,environmental engineering,noise control